2019
DOI: 10.1001/jamadermatol.2018.3715
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dapsone in the Treatment of Chronic Idiopathic and Autoimmune Urticaria

Abstract: IMPORTANCEThe first-line treatment for patients with chronic spontaneous urticaria (CSU), which is divided into idiopathic and autoimmune subtypes, consists of H 1 -antihistamines. However, limited evidence guides the treatment of CSU after maximal therapy with antihistamines fails. Two randomized clinical trials suggest that dapsone may be a successful second-line therapy.OBJECTIVE To evaluate the efficacy and safety of dapsone therapy in patients with CSU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 19 publications
0
11
0
3
Order By: Relevance
“…Immunotherapy is considered as a third line therapy and could be tried in patients with severe refractory autoimmune urticaria. Various immunosuppressants that have been tried in severe chronic urticaria include cyclosporine, methotrexate, sulphasalazine, dapsone, cyclophosphamide, and intravenous immunoglobulin [3][4][5][6][7][8]. In a recent placebo controlled study autohaemotherapy has shown a beneficial role in ASST positive chronic urticaria patients [9].…”
Section: Resultsmentioning
confidence: 99%
“…Immunotherapy is considered as a third line therapy and could be tried in patients with severe refractory autoimmune urticaria. Various immunosuppressants that have been tried in severe chronic urticaria include cyclosporine, methotrexate, sulphasalazine, dapsone, cyclophosphamide, and intravenous immunoglobulin [3][4][5][6][7][8]. In a recent placebo controlled study autohaemotherapy has shown a beneficial role in ASST positive chronic urticaria patients [9].…”
Section: Resultsmentioning
confidence: 99%
“…Dapsone was reported to be effective in several types of chronic urticaria and angioedema. In using dapsone to treat a skin disorder, a physician might start on a low dose of dapsone and gradually adjust the treatment dose to control the skin disease [ 81 ]. Dosage is based on the patient’s medical condition and response to treatment.…”
Section: Treatments Of Itch In Children and Adolescencementioning
confidence: 99%
“…These are rare but serious side effects, requiring close monitoring. Since the standardized age of use of these immunomodulators has not been well established, additional studies for proving long-term safety would be helpful [ 71 , 81 ].…”
Section: Treatments Of Itch In Children and Adolescencementioning
confidence: 99%
“…O mecanismo de ação na UCE não foi totalmente esclarecido, entretanto, os efeitos anti-inflamatórios da dapsona abrangem uma variedade de possíveis propriedades relevantes na urticária. Estas incluem interferência com a liberação ou função de enzimas lisossomais e com a geração de mieloperoxidase, mas, também interferência com a adesividade de neutrófilos mediada por integrina e inibição da atividade de prostaglandinas e leucotrienos 36,38,39 .…”
Section: Dapsonaunclassified